A Comparative Study of Spacecraft Charging Onset at Geosynchronous Altitudes: A Nonextensive Particle Approach. Issue 9 (14th September 2020) - Ali, S.; Rubab, N.; Nawaz, K.; Sarwar, S.
Abstract: Space plasma particlesand space weather conditions strongly affect spacecraft and satellites at geosynchronous Earth orbit (GEO) and their charging essentially occurs for incoming primary electrons and outgoing secondary and backscattered electrons. Due to the presence of high energetic (superthermal) electrons at GEO altitudes, a generalized power law q ‐nonextensive particle distribution is utilized to solve the current‐balance equation for spacecraft charging both analytically and numerically. The impact of subextensivity (q>1) and superextensivity (q<1) is discussed for plasma systems to analyze more pronounced energy tails associated with q  distribution as compared to standard Kappa distribution. The present findings indicate the suitability of proposed distribution for better describing the charge triggering as compared to Kappa and Maxwellian distributions. Furthermore, numerical estimation is made for identifying the current and charging onset due to various space grade materials. Key Points: Spacecraft charging in GEO Current‐balance equation with nonextensive approach Space‐grade materials